Evaluación del control interno al Comercial “Credifacil” del cantón Montalvo en el periodo 2022 - Jiménez Zamora, Danny Rafael (2023)
This research is part of the Evaluation of the internal control of the commercial “CREDIFACIL” of the Montalvo canton in the period 2022, for this the interpretation of the concepts related to the internal control systems and their assessment was carried out through different bibliographic sources. . That contribute to the conceptual development of the study, the case study and its analysis, in order to measure the weaknesses that the company has, based on qualitative and quantitative information, to later analyze the results, and thus obtain a panoramic view of the level. Of internal control with which the company operates, obtaining numerical data as evidence for its credibility, interpreting the adverse situations that the company faces, by not having planning and subsequently executing internal standards. Through surveys carried out with company workers, it was possible to verify the areas with the highest risk within the entity, in addition to inventories carried out on the merchandise, which was not found in its entirety or was found in poor condition, causing losses and a bad work environment for employees, since the company discounts each damaged or lost item. It was concluded that the company immediately needs the application of internal control systems that allow the company to generate policies and guidelines that guide the evaluation of control risks, their description and correction